Age Limit of Marriage in Islamic Family Law: A Comparative Study between Morocco, Pakistan, Malaysia, and Indonesia - Wafa, Zaein; Izzuddin, Ahmad; Rosidi, Achmad (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
The renewal of marriage laws in the Islamic world is not a new thing but has been debated since ancient times. The cause of these differences began with the rise of awareness from the community and scholars that the concept of Fiqh used was no longer in line with the times, so there needed to be a new legal reform that was in line with the demands of the Islamic community, especially in marriage in determining the age limit of marriage that occurred in Asian countries namely Morocco, Pakistan, Malaysia, and Indonesia. The development of knowledge about the situation and conditions of the developing community at that time was one of the factors that triggered family law reform. The method used in this writing is library research, with a legal analysis approach. so it involves an analysis of the legal regulations and provisions that apply in Islam. The regulation analysis carried out involves a comparison of family law in various countries related to the age limit of marriage. The discussion is interesting because it will provide consideration of the ideal age of marriage reviewed from the positive law of the country, and will know the historical side of the provision of age limits in marriage in comparative law in the country so that it is obtained in its application in the Islamic country it is different but not far from the age recommended in reaching adulthood and maturity of thinking, mental readiness because each country has its limits to measure the maturity of children to get married.